2021
DOI: 10.3920/wmj2020.2571
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of the antioxidant and antigenotoxicAchyrocline satureioides extract against zearalenone-induced mammal cytogenotoxicity and histological damage

Abstract: Zearalenone (ZEN), a Fusarium’s mycotoxin, is immunotoxic, genotoxic, hepatonephrotoxic and, affects the reproductive system. ZEN induces toxic and genotoxic effects on humans and other animals. Achyrocline satureioides has several medicinal properties. Moreover, the aqueous extract of A. satureioides is a safe agent that exerts low cytotoxicity and no genotoxicity. This extract is a promissory candidate to counteract ZEN effects. The present study aimed to investigate the capacity of cold aqueous extract from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Exposure to ZEN results in chromosomal aberrations, micronuclei, and DNA fragmentation. 96,97 A study found that exposing cells to ZEN resulted in DNA strand breaks. ZEN and its derivative α-ZOL had comparable DNA-damaging potential to the endogenous estrogens 17β-estradiol and estrone.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…Exposure to ZEN results in chromosomal aberrations, micronuclei, and DNA fragmentation. 96,97 A study found that exposing cells to ZEN resulted in DNA strand breaks. ZEN and its derivative α-ZOL had comparable DNA-damaging potential to the endogenous estrogens 17β-estradiol and estrone.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…Another study (Pinheiro et al, 2021) showed the effect of S. cerevisiae to feed contaminated with AFB 1 improving the performance indices of tambaqui (Colosoma macropomum). Sabini et al (2021) showed the efficacy of aqueous extracts of Achyrocline satureioides, a medicinal plant belonging to the Asteraceae family traditional from South America, which contain flavonoids that prevents the multi-target toxicity induced by ZEN.…”
Section: Control Strategies To Reduce the Impact Of Mycotoxicosismentioning
confidence: 99%
“…Consequently, the toxic effects and mechanisms of ZEN have been extensively studied by researchers all over the world. A number of studies have suggested that ZEN can cause damaging effects on a wide range of tissues and cells [ 5 , 6 , 7 ]. Of concern is the extreme vulnerability of mammalian enterocytes to the effects of mycotoxins in the gut [ 8 ].…”
Section: Introductionmentioning
confidence: 99%